Towards a framework for development of crowd logistics: Paving the way for sustainable logistics. (February 2023) - Samad, Taab Ahmad; Ganguly, Kunal K.; Das, Debabrata
Highlights: Research profile of the emerging field of Crowd logistics (CL) is presented. 79 articles are analyzed to retrieve and appraise factors affecting CL development. A framework to aid CL development is proposed and analyzed. Future research agenda is developed to validate and refine the proposed framework. Abstract: Crowd logistics (CL) can be understood as a concept in which logistics activities are outsourced to the occasional drivers selected from a pool of private or public travelers, and the operations are mediated by an online platform to attain benefits for the involved stakeholders. CL currently stands at a young state of maturity. Prior literature has identified the promising potential to help alleviate conventional business logistics' sustainability concerns, and researchers have advocated the need for extensive research for the future development of CL. However, the domain still lacks a developmental framework that explicitly studies factors affecting CL development and provides a roadmap for further growth. This study systematically reviews a portfolio of seventy-nine articles using the quantitative content analysis technique to identify the temporal trends in CL literature and collates lists of 11 barriers, 11 drivers, and 10 enablers to CL development. Following the systematic literature review, this study appraises the barriers, drivers, and enablers using content analysis and proposes a preliminary framework for CL development. At the theoretical level, we propose a developmental framework and supplement it with relevant recommendations for operationalization and testing, followed by several research questions to open avenues for future research. At a managerial level, our study helps practitioners with suggestions to adapt the proposed framework for CL businesses to foster sustainable CL systems. This study offers valuable insights about the factors that are currently driving [hindering] (or are likely to drive [hinder]) CL development and how the facilitating aspects can be explored to ensure further development of CL.